Dziewiętnastowieczne edycje literatury staropolskiej a światopogląd polskiego modernizmu. Rekonesans - Kacprzak, Marta M. (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2017)
1890–1918 was a time of intensive development of editorial works on literary texts, continuing workshop and ideological explorations in publishing work that started in the early nineteenth century. Chief editorial tasks and objectives were defined, principles were developed and a growing number of new editions of Old Polish works were made available. Did introducing them into readership and social awareness contributed to changing the outlook of the modernist era? Did historical phenomena, national traditions and myths found in traditional Polish literary works became a component of the modernist worldview thanks to those editions? The article is an invitation to examine an important aspect of publishing movement of 1890–1918, arguing that finding an answer to the question about the place of editions of Old Polish literature in the cultural and literary life as well as intellectual and artistic profile of Polish modernism may contribute to its specificity being recognised within European culture.